A dignidade da natureza ecológica a partir de Kant: uma releitura teleológica - Calgaro, Cleide (2020)
The present thesis seeks to depotentialize moral subjectivism and Kantian speciesism in order to extend the dignity to ecological nature based on the concept of contingent and sublime nature. In this way, the research aims to examine the possibility of expanding the Kantian concept of human dignity beyond speciesism, intending to apply it to nature in an ecological sense, from the study of the Critique of Judgment. The problem is established in how it is possible to expand the concept of dignity to nature in an ecological sense in Kant from his works. In the first chapter, we aim to analyze the concept of dignity in the work of Kant and what are the possible problems presented by the author. In the second chapter, we study the conceptualization of ecological nature and how it is seen in the three Kantian Critiques and in the essay On Perpetual Peace. A study of Kantian works is also envisaged in this chapter in order to obtain critical support to prove the proposed theme. In the end, in the third chapter, a critical analysis of Kantian dignity is made, especially from the Critique of Judgment, aiming to justify the research hypothesis according to which it is possible to expand the concept of dignity beyond a speciesist limitation towards ecological nature, in the sense that Kant offered elements to enhance nature and depotentialize subjectivism. Finally, the thesis concludes that in the moral and speciesist sense Kant will apply dignity to rational beings, however, in the expanded sense studied from the Critique of Judgment, it is observed that it is possible to extend dignity to ecological nature.